Implikasi Pendapatan Terhadap Kesejahteraan Keluarga Dengan Pengelolan Keuangan Sebagai Variabel Intervening Di Kelurahan Tonasa Kabupaten Pangkep - Bakhtiar Ass, Syamsul; Zalsabila, Adinda Thitania; Nur, Kherayani; Sarnawiah, Sarnawiah; Hajar, Hajar (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2024)
This study aims to determine the effect of income on family welfare through financial management as an intervening variable in Tonasa Village, Pangkep Regency. This type of research is quantitative using a questionnaire to 90 respondents. Data collection techniques are library research and field research. Data are processed using path analysis, correlation coefficient, determination coefficient, t-test, and sobel test using SPSS 25.0. The results of the first study showed that there was a positive and significant effect of income on family welfare. The results of the second study showed that there was no effect of income on financial management. The results of the third study showed that there was no effect of financial management on family welfare. Furthermore, the results of the fourth study showed that financial management was not able to be an intervening variable between income and family welfare.